Advantages of Heterofunctional Octyl Supports: Production of 1, 2‐Dibutyrin by Specific and Selective Hydrolysis of Tributyrin Catalyzed by Immobilized Lipases. Issue 12 (9th August 2016) - Hirata, Daniela B.; Albuquerque, Tiago L.; Rueda, Nazzoly; Sánchez‐Montero, Jose M.; Garcia‐Verdugo, Eduardo; Porcar, Raul; Fernandez‐Lafuente, Roberto
Abstract: Different lipases immobilized on octyl agarose or heterofunctional (glyoxyl or divinylsulfone) octyl supports have been compared in the selective and specific production of 1, 2‐dibutyrin by hydrolysis of tributyrin. The addition of cosolvents improved the solubility of the substrate thus improving the accumulation of 1, 2‐dibutyrin. The form B of the lipase from Candida antarctica (CALB) was selected considering reaction both enzyme activity and reaction yields produced by this biocatalyst. Using this enzyme, the highest dibutyrin yield using 100 mM of tributyrin (over 80 %) was obtained using a medium containing 50 % of cosolvent. However, the use of higher tributyrin concentrations required increasing the concentration of cosolvent in order to increase the soluble fraction of substrate. Under these conditions, the enzyme is released to the medium if it is just physically adsorbed on the support. For this reason, the octyl‐CALB biocatalyst is unsuitable for this reaction. Using octyl‐glyoxyl‐CALB in the presence of 75 % cosolvent to facilitate substrate solubility, a conversion yield of 70 % of dibutyrin could be achieved using 1 M of tributyrin as substrate. Using 500 mM tributyrin, the yield under these conditions increased to 80 %. The biocatalyst could be reused for several cycles without any detrimental effect on its performance. Abstract : lipase production of 1, 2 dibutyrin